2007
DOI: 10.1021/jf072041l
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Extracts from Defatted Rice Bran by Its Subcritical Water Treatment

Abstract: Defatted rice bran was extracted with water and subcritical water at 50-250 degrees C for 5 min. The highest extract yield was achieved at 200 degrees C, at which the maximum amounts of protein and carbohydrate were also obtained. The total phenolic and furfural contents, radical scavenging activity, and antioxidative activity for the autoxidation of linoleic acid increased with increasing treatment temperature. The bran extracts exhibited emulsifying activity except for the extract prepared at 250 degrees C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
75
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 45 publications
(54 reference statements)
10
75
0
1
Order By: Relevance
“…These observations suggest that proteinaceous substances be the main components in the extracts obtained at higher temperatures (16). However, the decrease of protein content at 220 and 240 °C suggested that at these temperatures the degradation of proteins and the generation of small components, such as organic acids, occur (17,18).…”
Section: Total Solid and Protein Contents And Ph Of Extractsmentioning
confidence: 97%
“…These observations suggest that proteinaceous substances be the main components in the extracts obtained at higher temperatures (16). However, the decrease of protein content at 220 and 240 °C suggested that at these temperatures the degradation of proteins and the generation of small components, such as organic acids, occur (17,18).…”
Section: Total Solid and Protein Contents And Ph Of Extractsmentioning
confidence: 97%
“…The antioxidative ability of the extract in the bulk oil system was evaluated by measuring the fraction of unoxidized linoleic acid by gas chromatography GC with some modifications 24,31 . Solutions of linoleic acid and the extract were prepared at 2.24 w/w by dissolving them in methanol to prepare the linoleic acid with 1 w/w of the extract.…”
Section: Antioxidative Ability In Bulk Oil Systemmentioning
confidence: 99%
“…Likewise, the treatment with supercritical carbon dioxide involves a great amount of carbon dioxide which is a predominant anthropogenic greenhouse gas. On the contrary, subcritical water treatment provides an environmentally friendly option for effective extraction of functional substances from food and agricultural wastes (Hata et al, 2008;Pourali et al, 2009;Watchararuji et al, 2008;Wiboonsirikul et al, 2007a;2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the treatment with supercritical carbon dioxide involves a great amount of carbon dioxide which is a predominant anthropogenic greenhouse gas. On the contrary, subcritical water treatment provides an environmentally friendly option for effective extraction of functional substances from food and agricultural wastes (Hata et al, 2008;Pourali et al, 2009;Watchararuji et al, 2008;Wiboonsirikul et al, 2007a;2007b).Subcritical water is water at over 100℃ that is compressed to maintain its liquid state below the critical point. The dielectric constant of water decreases from 80 to 27 with heating from room temperature to 250℃, which is similar to that of ethanol under ordinary pressure (Herrero et al, 2006;Miller and Hawthorne, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation